Changes in personality functioning following the end of psychotherapy [data] - Dönnhoff, Ivo; Kindermann, David; Stahl-Toyota, Sophia; Nowak, Jonathan; Orth, Maximilian; Friederich, Hans-Christoph; Nikendei, Christoph (Universität, 2025)
Abstract of the Study: Introduction: Although personality functioning has a long psychodynamic tradition and has received renewed interest in psychotherapy research with the DSM-5 and ICD-11, almost nothing is known about its course and influencing factors following psychotherapy. Methods: In a sample of 1208 completed psychotherapies from the Heidelberg Institute for Psychotherapy, we examined changes in personality functioning in the 1-year follow-up. We then used machine learning to filter out the probable predictors from all 277 possible predictors for changes in personality functioning following psychotherapy. Results: On average, the improvement in personality functioning remained stable following psychotherapy. However, it was found that patients whose personality functioning worsened during psychotherapy improved again following psychotherapy. Patients who improved particularly well during psychotherapy worsened slightly following psychotherapy. In total, we found 14 predictors for improved personality functioning following psychotherapy. Discussion: All the influences found suggest that the change in psychotherapy is in part influenced by how well the patient succeeds in internalising the insights gained in psychotherapy or the therapist. If this does not succeed, the patient cannot compensate for the loss of co-regulation by the therapist at the end of therapy and some of the improvements in psychotherapy are lost. For example, we found that with fewer than 20 hours of psychotherapy, it must be assumed that the patient will worsen in personality functioning following psychotherapy. From 20 hours onwards, the improvement remains stable and from 95 hours onwards, a subsequent improvement can be expected. Content: This dataset contains all of our R code we used to calculate our results. We have also uploaded RMarkdown HTML, so our peers may double check our results. We further included all results which we could not publish in our manuscript. Due to restrictions by the ethical review board, we are not allowed to upload any kind of RData-File which contains the raw data or an imputed dataset.